Effect of Work Environment and Transformational Leadership Style on Employee Performance of PT. Excelso Multi Rasa Outlet at Tunjungan Plaza Surabaya - Ika Prasetya Utami (Journal of World Conference (JWC), 2019)
The purpose of this study was to determine the effect of simultaneous and partial work environment and transformational leadership style on improving the performance of employees of PT. Excelso Multirasa Outlet at Tunjungan Plaza Surabaya. This research is quantitative research. Population and sample based on questionnaire distribution to employees of PT. Excelso Multirasa Outlet in Tunjungan Plaza Surabaya was taken as many as 45 respondents. Data collection techniques using interviews, observation and questionnaires. The data analysis used is reliability test, validity test, classic assumption test and multiple linear analysis test. The results of the study simultaneously and partially the work environment and transformational leadership style have a significant effect on the performance of employees of PT. Excelso Multirasa Outlet at Tunjungan Plaza Surabaya because of its significance <0.005.